2009
DOI: 10.1111/j.1473-6861.2009.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a lecturer in nurse education: the work‐place learning of clinical experts as newcomers

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…This analysis aligns broadly with the findings of previous research on the experiences of lecturers in nursing that identified a struggle for these academics to prioritise apparently conflicting areas of work especially research activity in a workplace characterised by excessive workload (Boyd & Lawley, 2009;Fisher, 2006;McArthur-Rouse, 2008). To some extent the excessive workload perceived by lecturers in professional fields may be attributed to the strong partnership with employers and with knowledge exchange and in the case of teacher educators a key aspect of this time-consuming work that has been termed 'relationship maintenance' (Ellis et al, 2014).…”
Section: Hyper-expansive Workplacessupporting
confidence: 51%
See 3 more Smart Citations
“…This analysis aligns broadly with the findings of previous research on the experiences of lecturers in nursing that identified a struggle for these academics to prioritise apparently conflicting areas of work especially research activity in a workplace characterised by excessive workload (Boyd & Lawley, 2009;Fisher, 2006;McArthur-Rouse, 2008). To some extent the excessive workload perceived by lecturers in professional fields may be attributed to the strong partnership with employers and with knowledge exchange and in the case of teacher educators a key aspect of this time-consuming work that has been termed 'relationship maintenance' (Ellis et al, 2014).…”
Section: Hyper-expansive Workplacessupporting
confidence: 51%
“…In the UK, lecturers in nursing and midwifery are often appointed on the basis of their clinical expertise and may begin their new academic career with no significant prior experience of research activity. This creates particular challenges for academic induction including the need to support research capacity building (Boyd & Lawley, 2009;Fisher, 2006, McArthur-Rouse, 2008. This approach to recruitment of lecturers in nursing has been found to create a conflict within departments and institutions in the value placed on knowledge and identity as a clinical expert and as a researcher (Barrett, 2006;Fisher, 2006;McNamara, 2010) and this conflict has been considered as a tension between 'rival knowledge regimes' (Findlow, 2012, p. 117).…”
Section: Insert Table One Herementioning
confidence: 99%
See 2 more Smart Citations
“…They may have a masters level qualification, but otherwise often have little or no direct experience of involvement in research activity. Small-scale qualitative studies have identified the considerable challenges faced by newly appointed academics in nursing (McArthur-Rouse, 2008;Boyd & Lawley, 2009). For academics in nursing there is a tension around the extent to which they should maintain more procedural knowledge in clinical skills and experience as well as propositional academic knowledge (Fisher 2006;Barrett, 2006;McNamara 2010) and this has been positioned as a tension between 'rival knowledge regimes' (Findlow 2012).…”
Section: Academic Identitymentioning
confidence: 99%